2013
DOI: 10.1093/jjco/hyt120
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of Patients with Non-muscle-invasive Bladder Cancer: Prognostic Value and Clinical Reliability of the 2004 WHO Classification System

Abstract: Objective: The aim of this study was to clarify the prognostic value and clinical reliability of the 2004 World Health Organization classification system of non-muscle-invasive bladder cancer. Methods: Between January 1995 and November 2010, 153 patients were diagnosed with nonmuscle-invasive bladder cancer. We used a substage system that discerns T1-microinvasive (T1m, 42 patients) and T1-extensive-invasive (T1e, 37 patients) cancers. Results: There were 2 (1.3%), 89 (58.2%) and 62 (40.5%) cases of Grade 1 -3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
(18 reference statements)
1
28
0
1
Order By: Relevance
“…subsequently proposed a 2‐mm cut‐off and, more recently, a 0.5‐mm cut‐off, which is pragmatically equivalent to one high‐power field, was proposed by van der Aa et al . The 0.5‐mm/one high‐power field cut‐off has been shown to be widely feasible and, in the majority of studies, correlated with outcome . Alternatively, Lopez‐Beltran et al .…”
Section: Stage Pt1 Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…subsequently proposed a 2‐mm cut‐off and, more recently, a 0.5‐mm cut‐off, which is pragmatically equivalent to one high‐power field, was proposed by van der Aa et al . The 0.5‐mm/one high‐power field cut‐off has been shown to be widely feasible and, in the majority of studies, correlated with outcome . Alternatively, Lopez‐Beltran et al .…”
Section: Stage Pt1 Carcinomamentioning
confidence: 99%
“…44 Amin et al and McKenney et al subsequently proposed a 2-mm cut-off and, more recently, a 0.5-mm cut-off, which is pragmatically equivalent to one high-power field, was proposed by van der Aa et al 40,42,43 The 0.5-mm/one high-power field cut-off has been shown to be widely feasible and, in the majority of studies, correlated with outcome. 42,[45][46][47][48][49][50] Alternatively, Lopez-Beltran et al proposed the cut-off to be 20 infiltrating tumour cells within the lamina propria rather than a linear measurement. 41 Specifically, with regard to papillary urothelial carcinoma, Lawless et al compared tumours with stalk-only invasion and focal tumour base invasion to tumours with extensive tumour base invasion, and found significantly worse outcomes in patients with extensive invasion.…”
Section: I C R O I N V a S I V E C A R C I N O M Amentioning
confidence: 99%
“…It is recommended that the tumour should be reported as high‐grade when variant histology such as this is present, despite the bland cytology, in order to reflect its biological behaviour . It is also evident that studies that graded invasive urothelial carcinoma using the 1973 WHO have demonstrated its prognostic significance . The WHO 2016 recommends grading of invasive urothelial carcinoma using criteria that are the same as in WHO 2004, recognising that the vast majority of tumours will be high‐grade (this recommendation is endorsed by the ICCR).…”
Section: Resultsmentioning
confidence: 99%
“…91 It is also evident that studies that graded invasive urothelial carcinoma using the 1973 WHO have demonstrated its prognostic significance. 82,84,92,93 The WHO 2016 recommends grading of invasive urothelial carcinoma using criteria that are the same as in WHO 2004, recognising that the vast majority of tumours will be high-grade (this recommendation is endorsed by the ICCR). If an alternative grading system is used concurrently, this should be indicated.…”
Section: Histological Tumour Gradementioning
confidence: 99%
“…Certains considèrent que la classification OMS/ ISUP2004 est supérieure à celle de l'OMS 1973 pour l'appréciation de la récidive et de la progression des tumeurs de vessie [10][11][12][13]. D'autres articles ne notent pas de diffé-rence significative entre les deux classifications pour évaluer l'évolution des tumeurs qui n'infiltrent pas la musculeuse [14,15].…”
Section: Critiques Dirigées Contre Cette Nouvelle Classification Oms/unclassified